Stem Cell Function, Self-Renewal, Heterogeneity, and Regenerative Potential in Skeletal Muscle Stem Cells - Cristini, Silvia; Alessandri, Giulio; Acerbi, Francesco; Tavian, Daniela; A. Parati, Eugenio; Invernici, Gloria (Recent Patents on Regenerative Medicine, 2012)
The main living element of the human body is the skeletal muscle. It is composed of myofibres and satellite cells, the adult stem cells responsible for skeletal muscle regeneration. Increasing confirmation suggests that satellite cells represent a heterogeneous population of cells with regenerative capacity and plasticity. Recent publications indicate numerous new findings in satellite and stem cells, from their developmental life and role as the main self-renewing myogenic stem cell in the adult skeletal muscle to their loss during aging. The present review is focused on skeletal muscle stem cells, including their identification, self-renewal ability, heterogeneity, and multilineage differentiation capacity. Finally, we summarize the latest developments, clinical applications and patents in regenerative medicine utilizing skeletal muscle stem cells.
Keywords: Muscle stem cell self-renewal